The Concept of Leadership from The Perspective of the Qur'an: A Thematic Study of Leadership Verses - Syahputra, Hari Risky; Mahmud, Hamidullah (Economic Reviews Journal, 2025)
This research aims to examine and explain in depth the concept of leadership from the perspective of the Qur'an through a descriptive qualitative approach with a thematic interpretation method (tafsir maudhui). The focus of the study is directed to verses that contain leadership values and principles, such as the caliphate, imamah, wali and ulil al-amr, which are the basis for the formation of the character and responsibilities of a leader in the Islamic view. The main data are obtained from the verses of the Qur'an and classical and contemporary tafsir such as Tafsir al-Ṭabari, Tafsir al-Qurṭubi, and Tafsir al-Mishbah. Through thematic analysis, this study found that the concept of leadership in the Qur'an is rooted in spiritual and moral values A leader in the view of the Qur'an is not only a holder of power, but also a servant of the ummah who is obliged to uphold justice, maintain trust, and direct society towards the common good. These values show that leadership in Islam has a strong ethical and social dimension, not just administrative or political. This research is expected to make a theoretical contribution to the development of the concept of Islamic leadership derived from the Qur'an and provide practical guidance for modern leaders in applying Qur'anic values in social and institutional contexts. The results of this study confirm that the Qur'anic leadership model is relevant to build a leadership system that is just, trustworthy, and oriented towards the benefit of the ummah.